Positive and Negative Aspects of Outsourcing - Franco, Mário (IntechOpen, 2018)
Outsourcing has been seen as a phenomenon allowing competitive advantages for organizations, but some studies do not include the causes and consequences of this particular strategy. Consequently, the objective of this book is to fill this gap by combining several studies from different perspectives. The various chapters presented here follow several approaches, which researchers explore in different contexts. This book intends, therefore, to add to the body of knowledge about outsourcing. Furthermore, it shows how the outsourcing strategy can stimulate organizations' development in various countries and regions worldwide.